(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article determines the choice of currencies which will be used in calculation of land assets. It grounds the necessity of evaluating land resources in Bitcoin crypto-currency which will guarantee their sufficient increase under conditions of national production stagnation. It stresses the necessity of formation of fundamentally new system of management of national economy and, in particular, land resources on the basic of Blockchain technology which will guarantee the reduction of buying-and-setting iteration and transparency of market price-setting. The use of the renewed system of management will allow to reduce risks of bankruptcy and illegal manipulations in the process of transfer of property rights for land resources.